Dupilumab treatment outcomes in bullous pemphigoid: a systematic review and single-arm meta-analysis - Chen, Yudi; Sun, Kailv; Chang, Jianmin (Frontiers in Immunology, 2026)
BackgroundBullous pemphigoid (BP) is the most common autoimmune subepidermal bullous disease of the skin. Novel biologic agents represent a potential therapeutic option. We explore the use of dupilumab in the treatment of BP.MethodsRelevant studies published up to Oct. 20th, 2025 were systematically searched using PubMed, Web of Science, Embase, and Cochrane Library. Proportion rates of complete response and disease control were analyzed to determine treatment effects. Data were quantitatively synthesized using a random-effects meta-analysis. Meanwhile, we also conducted statistics on adverse events.ResultsA total of 587 patients from 24 studies were included. Pooled analysis revealed a complete response rate of 68% (95% CI 60%∼78%) and disease control rate of 95% (95%CI 92%~98%) in BP treated with dupilumab with/without other systemic therapy. Notably, complete response rate achieved 63% (95% CI 49%∼81%) in patients with dupilumab without other systemic therapy. A total of 112 adverse events were reported in 97 patients. Most adverse events were mild and did not lead to treatment discontinuation.ConclusionThis meta-analysis highlights the efficacy and safety of dupilumab in patients with BP, offering valuable evidence to guide future clinical practice.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251048550.